Intraoperative neurophysiologic monitoring during cardiac surgery: an observational cohort study - James Brown; Kathirvel Subramaniam; Sarah Yousef; Ibrahim Sultan; Nidhi Iyanna; Derek Serna-Gallegos; Jianhui Zhu; Pyongsoo Yoon; David Kaczorowski; Johannes Bonatti; Danny Chu; Jeffrey Balzer; et al. (Open Heart)
Objective To evaluate the impact of intraoperative neuromonitoring (IONM) on stroke and operative mortality after coronary and/or valvular operations.Methods This was an observational study of coronary and/or valvular heart operations from 2010 to 2021. Baseline characteristics and postoperative outcomes were compared by the use or non-use of IONM, which included both electroencephalography and somatosensory-evoked potentials. Propensity-score matching was employed to assess the association of IONM usage with operative mortality and stroke.Results A total of 19 299 patients underwent a cardiac operation, of which 589 (3.1%) had IONM. Patients with IONM were more likely to have had baseline cerebrovascular disease (60% vs 22%). Patients with IONM had increased operative mortality (5.3% vs 2.5%) and stroke (4.9% vs 1.9%). Moreover, stroke and mortality were highly correlated, with 14% of strokes resulting in death, while only 2% of non-strokes resulted in death (p<0.001). The unadjusted Kaplan-Meier survival estimate was significantly lower among the group with IONM (p<0.001, log-rank). After propensity matching, however, there was no difference in operative mortality or stroke across each group: 3.6% vs 5.3% for mortality and 3.7% vs 5.4% for stroke. In the propensity-matched cohort, the Kaplan-Meier survival estimates were not significantly different across each group (p=0.419, log-rank).Conclusions Adjusting for baseline risk, there was no significant difference in adverse outcomes across each group. IONM may serve as a biomarker of cerebral ischaemia, and empirical adjustments based on changes may provide benefits for neurologic outcomes in high-risk patients. The efficacy of IONM during cardiac surgery should be prospectively validated.